Effects of Rice Straw and Its Biochar Addition on Soil Labile Carbon and Soil Organic Carbon - Yun-feng YIN; Xin-hua HE; Ren GAO; Hong-liang MA; Yu-sheng YANG (Journal of Integrative Agriculture, 2014)
Whether the biochar amendment could affect soil organic matter (SOM) turnover and hence soil carbon (C) stock remains poorly understood. Effects of the addition of 13C-labelled rice straw or its pyrolysed biochar at 250 or 350°C to a sugarcane soil (Ferrosol) on soil labile C (dissolved organic C, DOC; microbial biomass C, MBC; and mineralizable C, MC) and soil organic C (SOC) were investigated after 112 d of laboratory incubation at 25°C. Four treatments were examined as (1) the control soil without amendment (Soil); (2) soil plus 13C-labelled rice straw (Soil+Straw); (3) soil plus 250°C biochar (Soil+B250) and (4) soil plus 350°C biochar (Soil+B350). Compared to un-pyrolysed straw, biochars generally had an increased aryl C, carboxyl C, C and nitrogen concentrations, a decreased O-alkyl C and C:N ratio, but similar alkyl C and δ13C (1 742–1 877 ‰). Among treatments, significant higher DOC, MBC and MC derived from the new C (straw or biochar) ranked as Soil+Straw>Soil+B250>Soil+B350, whilst significant higher SOC from the new C as Soil+B250>Soil+Straw≈Soil+B350. Compared to Soil, DOC and MBC derived from the native soil were decreased under straw or biochar addition, whilst MC from the native soil was increased under straw addition but decreased under biochar addition. Meanwhile, native SOC was similar among the treatments, irrespective of the straw or biochar addition. Compared to Soil, significant higher total DOC and total MBC were under Soil+Straw, but not under Soil+B250 and Soil+B350, whilst significant higher total MC and total SOC were under straw or biochar addition, except for MC under Soil+B350. Our results demonstrated that the application of biochar to soil may be an appropriate management practice for increasing soil C storage.